2018
DOI: 10.1002/ajmg.c.31648
|View full text |Cite
|
Sign up to set email alerts
|

Less common manifestations in TSC

Abstract: Tuberous sclerosis complex (TSC) is due to pathogenic variants in TSC1 or TSC2 genes resulting in hyperactivation of the mTOR pathway. Many organ systems can be affected, such as brain, skin, eye, heart, bone, kidney, or lung. Typical lesions of TSC usually are those included as major criteria, including angiofibromas, hypomelanotic macules, tubers, subependymal nodules, angiomyolipomas, cardiac rhabdomyomas, and lymphangioleiomyomatosis. However, there are many other manifestations less frequent and/or less w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Differential diagnoses include shagreen patch, other hamartomas, and myelomenigocele. Fibrous dysplasia of bones is also a rare manifestation of TS 4 5. The index child had a spectrum of rare segmental osseocutaneous manifestations of TS.…”
mentioning
confidence: 99%
“…Differential diagnoses include shagreen patch, other hamartomas, and myelomenigocele. Fibrous dysplasia of bones is also a rare manifestation of TS 4 5. The index child had a spectrum of rare segmental osseocutaneous manifestations of TS.…”
mentioning
confidence: 99%
“…Aneurysm formation may be related to improper differentiation of smooth-muscle cells as a result of disruption of the mammalian target of rapamycin (mTOR) signaling pathway, impairing the structural integrity of the smoothmuscle cells within the vascular wall. 61 Histological analysis of an intracranial aneurysm in a patient with TSC demonstrated hypocellular hyaline fibrous tissue without necrosis or inflammation, and microscopic examination of a TAA in a patient with TSC found that most normal cellular structures had disappeared. 62,63 There are case reports of aortic aneurysms reported in patients with TSC, the majority of which were found prior to the age of 10 years, 64 but no larger series studies.…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 95%
“…When compared to the general population of all ages, the incidence of intracranial aneurysms in patients with TSC was approximately twice as high. 61,65 A recent review found that intracranial aneurysms in patients with TSC were large, fusiform, and located primarily in the ICA, a pattern that differs from aneurysm formation in the general population. 66,67 This review also found that twothirds of these patients were pediatric patients, again suggesting early and rapid aneurysm formation and growth.…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 99%
“…Although these strategies can be used to grow TSC expertise in each region, health care for a person with TSC will occasionally benefit from specific expertise beyond their regular team of health care providers. For example, a younger child with seizures that are not responding to firstand second-line therapies; an adult diagnosed with possible renal cell carcinoma by a urologist or nephrologist who is unfamiliar with TSC; a person with TSC with a less common sign or symptom of TSC (e.g., bone lesions 25 ). Lead patient education on the guidelines at a global level, particularly for key information gaps such as medical warning signs, or "red flags," for various signs of TSC.…”
Section: Priority 1 Recommendationsmentioning
confidence: 99%